Tantalizing Maria : the temptation saga : book seven - Hardt, Helen (Hardt, Helen. Temptation saga, 2016)
Maria Gomez married her lover<U+2019>s brother to give the baby she carried the name and future she deserved. Now she is widowed, and her oldest child<U+2019>s father<U+2014>the only man she ever loved<U+2014>has returned. In prison for a crime he didn<U+2019>t commit, Jefferson Bay never forgot the beautiful woman who betrayed him with his own brother. When DNA evidence proved Jeff<U+2019>s innocence years later and he was released, he vowed to find Maria and seek his revenge. The passion between the two has never died, but can they learn to trust each other again?